Evolution of high-speed rail and its development effects: Stylized facts and review of relationships - Shreyas Bharule; Tetsuo Kidokoro; Fumihiko Seta (Asian Development Bank Institute (ADBI), 2019)
The potential effects of high-speed rail (HSR) reach into many overlapping fields of interest. This paper summarizes the evolution of HSR and elaborates on the development effects of the HSR transport infrastructure. HSR can simultaneously become a core component on desired urban developments, while also having undesirable outcomes. Positive impacts will be achieved only if interactions with other factors and contexts are maintained. This paper stratifies and expands the understanding of the development effects of HSR at three levels - regional, urban, and station area - based on the economic and temporal nature of all infrastructure projects. There is ample evidence that at the regional level, the implementation of an HSR service disrupts the existing network of cities along the proposed corridor. The HSR network changes the accessibility of a locality. Better accessibility will change the mobility patterns and will eventually affect the development in the impacted region, reshaping the entire urban-regional system. The HSR is expected to play a catalyzing role in driving the spatial and urban transformation process. This paper emphasizes the importance of establishing a synergy between HSR and urban development. A synergy between HSR and other elements, like urban transit facilities, paratransit, station area development, node, and sub-center development, can usher in spatial and economic development, but an institutional arrangement across all the elements is of paramount importance. Such a synergy would enhance livability and provide improved quality of life opportunities in cities and regions served by HSR. Last, an HSR corridor is beneficial both to the settlements along the corridor and to the railway operator. An HSR corridor is also beneficial to the cities along the railways, and the station areas provide an important opportunity to harness revenue through non-railway businesses. However, achieving the full development effects of an HSR project may take decades. Careful pre-planning of the project and coordination amongst the stakeholders are necessary to accomplish a set of phased goals to realize the envisioned development of an HSR corridor.
Keywords: O18; R11; R12; R52; R58; 330; high-speed rail; regional development; urban development; station area development